Drawing therapy to improve the quality of life for children victims of landslides - Elli Nur Hayati; Inda Purwasih; Siti Urbayatun (Universitas Ahmad Dahlan, 2019)
Disasters may affect the quality of life of survivors, including children. Therefore, interventions that may improve survivors' quality of life is needed. The purpose of this study is to determine the effect of drawing therapy in improving the quality of life of children survivors of landslides in Purworejo, Central Java, Indonesia. This study used a quasi-experimental design with one group pretest - posttest. The subjects were five children aged 8 to 11 years who experienced a landslide disaster, and had low or moderate quality of life based on WHOQOL-BREF scale categorization. The experimental group was treated using therapeutic techniques that facilitated the subject to externalize their traumatic experiences through creative actions that reflected their feelings and thoughts. Therapy was done through three stages of warm up, mindfulness, and drawing. The results of the Friedman Test analysis show the differences in the quality of life scores in all domains before and after the intervention was given. Qualitative data that was taken as complimentary to the quantitative part also showed a description of improved behavior, attitudes, and social interactions among the children. It is concluded that drawing therapy can improve the quality of life of the children survivors of a landslide disaster.